Diclofenac biotransformation and toxicity assessment of laccase from Pleurotus floridanus - Chenthamara, Dhrisya; Ramakrishnan, Sankar Ganesh; Khusro, Ameer; Subramaniam, Sadhasivam; Alghamdi, Saad; Almehmadi, Mazen; Kabrah, Ahmed; Sahibzada, Muhammad Umar Khayam; Eftekhari, Aziz (Cellular and Molecular Biology, 2022)
Laccase producing fungus Pleurotus floridanus was isolated from Siruvani forest, Tamil Nadu, India. The potential of P. floridanus to produce laccase by using various lignocellulosic substrates was screened under submerged fermentation. Laccase production in the presence of lignocellulosic substrates such as rice, wheat and maize bran as a sole source of carbon as well as an additional supplement was examined. Laccase activity of P. floridanus using varied substrates was observed in the order of rice bran > wheat bran > maize bran. The isolate showed maximum laccase activity of 13.29±0.01 U/mL using rice bran as a carbon source within 11 days. This was 18 fold higher than the control media that lacks lignocellulosic substrates. The diclofenac tolerance was assessed in solid media at various concentrations and the results showed that the mycelia growth is not significantly affected by the drug. Finally, the laccase mediated degradation of diclofenac at a concentration of 10 mg/L showed 98% degradation in 2 h. The phytotoxicity of the crude laccase treated diclofenac was lower than the untreated diclofenac. In conclusion, findings suggested direct application of crude laccase produced from P. floridanus using agro-residues as ideal substrate for environmental applications.